Phosphorylated α(1→4)Glucans as Substrate for Potato Starch-Branching Enzyme I - Viksø-Nielsen, Anders (American Society of Plant Physiologists, 1998)
The possible involvement of potato (Solanum tuberosum L.) starch-branching enzyme I (PSBE-I) in the in vivo synthesis of phosphorylated amylopectin was investigated in in vitro experiments with isolated PSBE-I using (33)P-labeled phosphorylated and (3)H end-labeled nonphosphorylated α(1→4)glucans as the substrates. From these radiolabeled substrates PSBE-I was shown to catalyze the formation of dual-labeled ((3)H/(33)P) phosphorylated branched polysaccharides with an average degree of polymerization of 80 to 85. The relatively high molecular mass indicated that the product was the result of multiple chain-transfer reactions. The presence of α(1→6) branch points was documented by isoamylase treatment and anion-exchange chromatography. Although the initial steps of the in vivo mechanism responsible for phosphorylation of potato starch remains elusive, the present study demonstrates that the enzyme machinery available in potato has the ability to incorporate phosphorylated α(1→4)glucans into neutral polysaccharides in an interchain catalytic reaction. Potato mini tubers synthesized phosphorylated starch from exogenously supplied (33)PO(4)(3−) and [U-(14)C]Glc at rates 4 times higher than those previously obtained using tubers from fully grown potato plants. This system was more reproducible compared with soil-grown tubers and was therefore used for preparation of (33)P-labeled phosphorylated α(1→4)glucan chains.